2019
DOI: 10.3390/ma12244146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antibacterial Silver-Releasing Filler on the Physicochemical Properties of Poly(Methyl Methacrylate) Denture Base Material

Abstract: Colonization of polymeric dental prosthetic materials by yeast-like fungi and the association of these microorganisms with complications occurring during prosthetic treatment are important clinical problems. In previously presented research, submicron inorganic particles of silver sodium hydrogen zirconium phosphate (S-P) were introduced into poly(methyl methacrylate) (PMMA) denture base material which allowed for obtaining the antimicrobial effect during a 90 day experiment. The aim of the present study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 108 publications
1
24
0
Order By: Relevance
“…However, we observed that the higher ratios of particles led to appearances of clustering, which form spaces. The spaces could explain the decreased strength of the material and the non-homogeneous mixing [ 7 , 12 , 37 ]. This is supported by the SEM images presented in Figure 4 B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we observed that the higher ratios of particles led to appearances of clustering, which form spaces. The spaces could explain the decreased strength of the material and the non-homogeneous mixing [ 7 , 12 , 37 ]. This is supported by the SEM images presented in Figure 4 B.…”
Section: Discussionmentioning
confidence: 99%
“…PMMA has been a preferred choice in the production of denture bases since its introduction in 1930s [ 5 , 6 ]. While dental implants are increasingly being used as substitutes for natural teeth in both partially dentate and edentulous patients, PMMA remains the preferred choice for denture base construction [ 7 ]. The popularity of PMMA as a polymeric material among those currently available can be attributed to its functional properties [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…3-Trimethoxysilyl propyl methacrylate silane (γ-MPS) can enhance the strength of a bond between a filler material and a given acrylic matrix by nurturing the formation of covalent bonds and a hydrophobic surface [ 43 ]. As the nanoparticles offer a large surface area that generates a high level of surface energy, they exhibit a strong propensity to aggregate [ 3 ]. If such aggregation occurs, the chemical interaction between the base PMMA and the nanoparticles may reduce [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the nanoparticles offer a large surface area that generates a high level of surface energy, they exhibit a strong propensity to aggregate [ 3 ]. If such aggregation occurs, the chemical interaction between the base PMMA and the nanoparticles may reduce [ 3 ]. As such, a 3 wt.% silane coupling agent was employed in the current study with the underlying intention of increasing the chemical adhesion between the surface of the filler and the PMMA as a means of producing functional groups [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation